Generational Models in Nursing Administration in the Ambulatory Care Nursing Service Division - ศรีประสาร พัชระกรพจน์; Sujintawong, Suchat (Journal of Public Health Nursing, 2019)
Generational differences by age often dictates nurse’s needs and affects nursing operations in healthcare organizations. There is a need for nursing administrators to understand and learn the unique characteristics of nurses in each age range. This will ensure adaptive nurse administration in the organization, including appropriate assignment of workload for the different needs of nursing personnel by each age and bring work satisfaction in the organization. This article considers three main factors: 1) Generational age groups: Baby Boomers, Generation X and Generation Y, 2) Nursing Administration, and 3) Shared Governance Models in developing guidelines for nursing administration in the Ambulatory Care Nursing Service Division, Nursing Department, Faculty of Medicine, Ramathibodi Hospital. Age ranges by age division were: Baby Boomers were between 52 and 60 years old, Generation X was between 40-51 years of age and Generation Y, between 20-39 years. Nursing administration concepts for each group were used to developed meaningful leadership and practice for optimal work outcomes. This example illustrates how a guideline for nurse administrators can be applied to manage nurse personnel in an organization based on knowledge, understanding, beliefs, attitudes and behaviors by generational group. This can be an important driving force to enable healthcare organizations to achieve their goals.